METHOD OF PREDICTING ANIMAL LITTER SIZE USING PROTEIN BIOMARKERS RELATED WITH FERTILITY, AND METHOD OF PREDICTING ANIMAL SPERM QUALITY AND LITTER SIZE USING CHLORTETRACYCLINE STAINING - KWON, WOO SUNG; PAGN, MYUNG GEOL (2016)
The present invention relates to a method for predicting an animal litter size by using a protein marker related to fertility and, more specifically, to a litter size prediction marker composition for discovering a marker of a sperm differently expressed according to the litter size production ability of an animal and including an antibody specifically coupled with the marker and to a method for predicting an animal litter size by using the same. The present invention also relates to a method for predicting an animal sperm quality and an animal litter size by using a chlortetracycline coloration scheme and, more specifically, to a method for predicting an animal litter size by measuring mobility, kinematics, or fertility capacitance of a sperm. By using the protein marker derived from an animal sperm according to the present invention, a litter size production ability may be predicted through an analysis of a protein differently expressed according to a litter size production ability. By using the method for predicting an animal sperm quality and an animal litter size by using a chlortetracycline coloration scheme, fertility of a sperm and a litter size production ability of an entity may be predicted. Thus, according to the present invention, an excellent species having high sperm fertility and a high litter size production ability is sorted on the basis of information provided by the method, so the same may be very useful in promoting the stable production of animals. 본 발명은 수태능력 관련 단백질 마커를 이용한 동물의 산자수 예측 방법에 관한 것으로서, 더욱 상세하게는 동물의 산자수 생산 능력에 따라 달리 발현되는 정자의 마커를 발굴하고, 상기 마커에 특이적으로 결합하는 항체를 포함하는 산자수 예측용 마커 조성물 및 이를 이용하여 동물의 산자수를 예측하는 방법에 관한 것이다. 본 발명은 또한, 클로르테트라사이클린 염색법을 이용한 동물의 정액 품질 및 산자수의 예측 방법에 관한 것으로서, 더욱 상세하게는 정자의 운동성, 운동학 또는 수정능획득(capacitance) 상태를 측정하여 동물의 산자수를 예측하는 방법에 관한 것이다. 본 발명에 따른 동물의 정자 유래 단백질 마커를 이용하여 산자수 생산 능력에 따라 달리 발현되는 단백질의 분석을 통해 개체의 산자수 생산 능력을 예측할 수 있으며, 클로르테트라사이클린 염색법을 이용한 동물 정액 품질 및 산자수의 예측 방법을 이용하여 정자의 수정능력 및 개체의 산자수 생산 능력을 예측할 수 있다. 따라서 본 발명은 상기 방법에서 제공되는 정보를 기반으로 정자의 수정능력이 높고, 산자수 생산 능력이 높은 우수 종을 선별하여 동물의 안정적 생산을 도모하는 데 매우 유용하게 사용할 수 있을 것이다.